The Role of Digital School-Home Communication in Teacher Well-Being - Kuusimäki, Anne-Mari; Uusitalo-Malmivaara, Lotta; Tirri, Kirsi (Frontiers in Psychology, 2019)
Well-functioning communication is crucial in all work communities. A respectful and trusty partnership between parents and teachers in schools is essential not only for pupils but also for the well-being of the whole organization. Communication is at the heart of such a partnership. Although most parent-teacher communication nowadays takes place on digital platforms, not much is known about the specific role of digital communication (DC) in building parent-teacher partnerships. In an attempt to find out we asked 400 Finnish parents and 80 teachers about their experiences of communicating digitally and the kind of matters they discussed, and how they thought feedback on pupils should be expressed. The data was content- analyzed. Three categories related to DC content were identified: study-related matters, behavioral issues, and sensitive issues. Parental and teachers’ expectations of how pupil feedback should be expressed also fell into three categories: a good balance of encouraging and corrective feedback, more encouraging feedback, and a constant emphasis on the child’s weaknesses. These results have research and practical implications for teacher well-being.